Skeletal parallel programming - Saez, Fernando (2007)
In the last time the high-performance programming community has worked to look for new templates or skeletons for several parallel programming paradigms. This new form of programming allows to programmer to reduce the time of development, since it saves time in the phase of design, testing and codification. We are concerned in some issues of skeletons that are fundamental to the definition of any skeletal parallel programming system. This paper present commentaries about these issues in the context of three types of D&C skeletons.